Autism and criminal justice : the experience of suspects, defendants and offenders in England and Wales - Smith, Tom (Thomas) (Lecturer in law) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This collection presents a summary of current knowledge regarding autistic suspects, defendants and offenders in the criminal justice system of England and Wales. The volume examines the interaction between each stage of the criminal justice process and autistic individuals accused or convicted of crime, considering the problems, strengths, and possibilities for improving the system to better accommodate the needs of this vulnerable category of neurodiverse individuals. By explicating the core issues in this important but disparate area of study in a single place, the collection facilitates understanding of and engagement with knowledge for a wider audience of relevant stakeholders, including criminal justice practitioners, policy makers, academics and clinicians. It also incorporates key recommendations for improvement, thereby clarifying the urgent need for substantive change in policies and practices. The ultimate goal is to both improve the treatment and experience of autistic people subjected to criminal justice processes; and produce fairer, more appropriate systemic outcomes. While focused on the criminal justice system of England and Wales, the work will be valuable for researchers and policy-makers working in similar systems, as well as those interested in neurodiversity more generally"--
'Street' policing and autism: perceptions and preconceptions of police officers when interacting with autistic suspects in the community / Shirley Reveley and Iain Dickie -- Autistic suspects in police custody: issues affecting the effectiveness and fairness of police interviews / Clare Allely and David Murphy -- Autistic defendants in court: perceptions and support for accessing justice -- / Clare Allely, Eddie Chaplin, Jody Salter, Jane McCarthy, Felicity Gerry KC -- Autism in prisons: an overview of experiences of custody and implications for custodial rehabilitation for autistic prisoners / Luke P Vinter and Gayle Dillon.
OCLC-licensed vendor bibliographic record.
Keywords: Offenders with mental disabilities -- England; Offenders with mental disabilities -- Wales; Special needs offenders -- England; Special needs offenders -- Wales; Discrimination in criminal justice administration -- England; Discrimination in criminal justice administration -- Wales; Autistic people -- Legal status, laws, etc. -- England; Autistic people -- Legal status, laws, etc. -- Wales; LAW / General; LAW / Civil Rights; LAW / Criminal Law / General